2000
DOI: 10.1046/j.1524-475x.2000.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

An economic assessment of Apligraf® (Graftskin) for the treatment of hard‐to‐heal venous leg ulcers

Abstract: Several recent advances in wound care may offer promise for the treatment of hard-to-heal venous leg ulcers. One such treatment is Apligraf (Graftskin), a bilayered, living human skin construct. To assess the economic impact of Graftskin, a model was constructed to compare the annual medical costs and cost-effectiveness of treating hard-to-heal venous leg ulcers with Graftskin vs. compression therapy using Unna's boot. A semi-Markov model was used to describe the pattern of ulcer treatment, healing, and recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 13 publications
3
46
0
Order By: Relevance
“…Previous cost-effectiveness analyses have found similar results when assessing the relative costs and benefits of CTPs in the management of VLUs. Schonfeld et al [31] evaluated the cost-benefit of HSE in comparison to Unna's boot as the standard care using a semi-Markov model over a horizon time of 1 year and found that rates of healing in the HSE group were approximately 48.1% compared with 25.2% in standard care patients. Annual costs for HSE patients were slightly more expensive than the annual cost for Unna's boot patients ($12,807 vs. $10,482, respectively; 1996 US dollars), with a calculated ICER of $800 per additional month of healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous cost-effectiveness analyses have found similar results when assessing the relative costs and benefits of CTPs in the management of VLUs. Schonfeld et al [31] evaluated the cost-benefit of HSE in comparison to Unna's boot as the standard care using a semi-Markov model over a horizon time of 1 year and found that rates of healing in the HSE group were approximately 48.1% compared with 25.2% in standard care patients. Annual costs for HSE patients were slightly more expensive than the annual cost for Unna's boot patients ($12,807 vs. $10,482, respectively; 1996 US dollars), with a calculated ICER of $800 per additional month of healing.…”
Section: Discussionmentioning
confidence: 99%
“…The longer it takes to heal an ulcer, the greater the financial burden to the health care system [29]. Controlled clinical studies have shown that HSE is more economical and effective at healing chronic VLUs than is standard care alone [30,31]. Schonfeld et al [31] reported that the estimated average direct cost (US dollars) of care for VLUs treated with HSE was $12,807 compared with $10,482 with Unna boot therapy; moreover, patients treated with HSE had almost 3 additional healed months (4.60 vs. 1.75, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaulyanov et al, reviewed several clinical studies on both DFU and VLU with BBSS treatment. BBSS has been determined as more effective and economical at healing chronic VLU [16][17][18] and DFU [19] than standard wound care therapy alone [19]. BBSS has been shown to reduce the risk of development of osteomyelitis and amputation in diabetic patients (Table 5).…”
Section: Healed Ulcer (N)mentioning
confidence: 99%
“…Among ulcers present for a year or longer, a theoretical semi-Markov model suggested that both annual costs ($20, 041 versus $24, 493) and healed months per year (4.60 versus 1.75) favored the use of Apligraf over paste bandages. 38 However, another cost analysis suggested that the incremental cost to achieve an additional successfully treated patient was $1600 ($1600 -$6400), $3150 ($1890 -$24, 570) and $29, 952 ($14,976 -$119,808) for Talymed, Oasis, and Apligraf respectively.…”
Section: Wound Dressings For Chronic Venous Ulcersmentioning
confidence: 99%